Teachers’ and Students’ Perception on Teaching and Learning Speaking Skills - Kandel, Shree Krishna (NELTA Bagmati Journal, 2022)
This paper explored teachers’ and students’ perceptions on their teaching and learning English-speaking skills in a community school. It explored their perceptions based on in-depth interviews with six teachers and fifteen students from community schools in Nuwakot, Dhading, and Kathmandu districts. The discussion was limited to teaching techniques, methods, students’ participation, and teachers’ facilitation during teaching. The study made the findings that students are not provided with appropriate time and attention in teaching and learning speaking skills. Students preferred adequate time in daily teaching-learning for speaking skills, which was lacking in practise. Furthermore the student participants suggested to include sufficient speaking activities and exercises in the textbook. The study also found that weak students who showed comparatively less participation in speaking activities were to be encouraged for their proactive involvement in the learning process.